The extent to which adequacy of staffing predicts nursing teamwork in hospitals - Helga Bragadóttir; Beatrice J. Kalisch; Gudný Bergthóra Tryggvadóttir (Journal of Clinical Nursing)
Aims and objectives The purpose of this study was to examine the extent to which staffing adequacy predicts nursing teamwork, controlling for demographic and background variables. Background Findings from former studies indicate that hospital, unit and staff characteristics may be related to nursing teamwork, such as type of hospital and unit, role, gender, age, work experience, type of shift worked, shift length, number of working hours per week, overtime and staffing adequacy. Teamwork as well as staffing is identified as significant contributors to patient and staff safety in hospitals. However, the contribution of staffing to the quality of nursing teamwork is scarcely studied. Design This was a quantitative descriptive cross‐sectional study using the paper‐and‐pencil questionnaire Nursing Teamwork Survey‐Icelandic. Methods The study was conducted in 27 inpatient units in eight hospitals in Iceland with a sample of 925 nursing staff members. Participants were 567 registered nurses, practical nurses, unit secretaries and nurse unit managers. The Strengthening the Reporting of Observational Studies in Epidemiology checklist was used for this paper. Results When controlling for unit type, role, experience on current unit and intent to leave, perceived adequacy of staffing alone explains up to 10% of overall teamwork. Unit type, role, years of experience on current unit and perceived staffing adequacy correlated significantly with overall teamwork. Conclusions The findings of this study indicate that unit and staff characteristics, including perceived adequacy of staffing, are associated with and explain the variability in nursing teamwork on inpatient hospital units. The findings of this study provide important information for clinical nurses, nurse managers, policymakers and instructors in health care. Relevance to clinical practice The findings underline the importance of adequate staffing for nursing teamwork in inpatient hospital units.